The use of ruthenium Y zeolite catalysts for the selective methanation of carbon monoxide - Ahmed, Zaheera (Department of Chemical Engineering, 2016)
Fuel processing is the conversion of hydrocarbons to produce a mixture of H2 and CO, whereby the H2 will be used in a PEMFC. CO needs to be removed as the tolerance level of the Pt based electro catalyst is only 10 ppm of CO. In order to lower the concentration from 1% post-WGS, to 10 ppm, CO can be converted to CH4 via selective methanation. A selective catalyst primarily methanates CO and inhibits the methanation of CO2 which results in the over consumption of H2. Common catalysts for SMET include Ru/Al2O3 and Ru/Y zeolites. This study involved the use of Ru/Y zeolite catalysts with loadings between 1 wt.%-5.4 wt.% Ru prepared via ion exchange, and a commercial 5 wt.% Ru/Al₂O3. These catalysts were tested in a fixed bed reactor at temperatures between 160°C and 210°C at various space velocities with a feed composition of 1% CO, 20% CO2, 10% H2O, 59% H2 and 10% Ar. The effects of loading, space velocity and reaction temperature on the CO conversion and CO selectivity were investigated. The 2.2 wt.% was found to be the optimum loading by displaying the highest selectivity of 72%, and 100% CO conversion at 170°C. The higher loadings produced large amounts of CH4 displaying lower selectivity, coupled with a high undesirable consumption of H2. The 1 wt.% Ru/Y zeolite showed low activity for SMET but was active for the WGS reaction. The 5 wt.% Ru/Al2O3 displayed the highest selectivity of 60%, and 100% CO conversion at 180°C.